Politik Hukum Dalam Menangani Pertanahan Agraria Di Indonesia (International Forum of Researchers and Lecturers, 2025)
Agraria law is the law that regulates relations between people and land and other people. Sudikno Mertokusumo explained that the law, also known as land law, is the interest of people in other people regarding land. According to Subekti, agrarian law is the totality of legal provisions, whether civil, state administration or state administration law, which also regulates authorities that originate from certain relationships. For information, the basis of agrarian law is regulated in Law Number 5 of 1960 concerning basic regulations on agrarian principles or UUPA. In this agrarian law regulation, there are at least seven principles1. These are: the principle of control by the state, the principle of social function, the principle of customary law, the principle of nationality or nationhood, the principle of limiting land ownership for the sake of the public interest, the principle of general planning and the principle of land preservation. From various literature it is known that the history of the birth of the UUPA tells the long history of the struggle of national figures in reducing the impartiality of land law for the benefit of society at large. In the era of reform, the logical consequences between political existence and interests and legal certainty, especially regarding land issues, have become a trending topic that is interesting to discuss. The complexity of land issues in this country is increasingly increasing and complicated, and is exacerbated by friction between interests that are politically charged. Legal politics consists of a series of words politics and law. (Suderto, et., al 1983) explains that politics is used in various meanings, namely: 2 1. The word polik in Dutch, which means something related to the State 2. Means discussing state issues or those related to the State Furthermore, Sudarto emphasized that the meaning of politics is policy which is a synonym for policy. In this sense, the words economic politics, crime, legal politics and criminal law politics are found. The relationship between politics and law, according to (Mahfud et., al 1998) explains that law is a political product. Law is seen as an independent variable (variable influence) and politics as an independent variable (variable influence). With this assumption, Mahfud formulated the law as: 3 Legal policies that will be or have been implemented nationally by the government also include an understanding of how politics influences the law by looking at the configuration of forces behind the creation and enforcement of the law. Here the law is not only seen as articles that are imperative or mandatory, but must be seen as a sum system which in reality is not impossible, in fact it is not impossible which is very much determined by politics, both in the formulation of material and articles and in implementing them.